2013
DOI: 10.1210/jc.2013-1169
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Midday Moderate-Intensity Exercise on Postexercise Hypoglycemia Risk in Individuals With Type 1 Diabetes

Abstract: The pattern of glucose requirements to maintain euglycemia in response to moderate-intensity exercise performed at midday suggests that the risk of exercise-mediated hypoglycemia increases during and for several hours after moderate-intensity exercise, with no evidence of a biphasic pattern of postexercise risk of hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 32 publications
2
46
0
3
Order By: Relevance
“…In a euglycemic clamp in which exercise was performed in the afternoon (4 p.m.), MacMahon et al [53] showed that glucose infusion rates necessary to maintain stable glycemia peaked in a biphasic manner: during exercise and early recovery, plus in the night afterwards (midnight to 4 a.m.). Conversely, in an otherwise equivalent design with exercise performed at midday, Davey et al [54] did not observe the same biphasic behavior in the glucose infusion rates, which were elevated for 11 h postexercise. It is difficult to draw solid conclusions in this regard from the included studies: all but three experiments were carried out in the morning; with the exceptions of Maran et al [33] (exercise at approximately 2 p.m.), Iscoe and Riddell [31], and Yardley et al [28] (both at 5 p.m).…”
Section: Strengths and Limitationsmentioning
confidence: 86%
“…In a euglycemic clamp in which exercise was performed in the afternoon (4 p.m.), MacMahon et al [53] showed that glucose infusion rates necessary to maintain stable glycemia peaked in a biphasic manner: during exercise and early recovery, plus in the night afterwards (midnight to 4 a.m.). Conversely, in an otherwise equivalent design with exercise performed at midday, Davey et al [54] did not observe the same biphasic behavior in the glucose infusion rates, which were elevated for 11 h postexercise. It is difficult to draw solid conclusions in this regard from the included studies: all but three experiments were carried out in the morning; with the exceptions of Maran et al [33] (exercise at approximately 2 p.m.), Iscoe and Riddell [31], and Yardley et al [28] (both at 5 p.m).…”
Section: Strengths and Limitationsmentioning
confidence: 86%
“…The effect of physical exercise on the severity and risk of hypoglycaemia was a subject of few literature reports only [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…It could also be speculated that the anticipation to changing glucose levels is complicated by prolonged exercise. For example, the insulin-to-carbohydrate ratio required to maintain euglycemia is strongly altered during and following exercise [26]. Inadequate adjustment of pre-and post-exercise insulin use could result in exaggerated up-or downward glucose excursions [9].…”
Section: Discussionmentioning
confidence: 99%